2022
DOI: 10.17645/mac.v10i4.5623
|View full text |Cite
|
Sign up to set email alerts
|

States vs. Social Movements: Protests and State Repression in Asia

Abstract: This study considers how governments use state-sponsored propaganda and state violence in tandem to repress social movements and, in so doing, exacerbate polarization. We specifically focus on cases in young and non-democracies in East and Southeast Asia: China and Hong Kong, the Free Papua Movement in Indonesia, and Myanmar’s more recent coup. Using a time series analysis, our analysis reveals a temporal relationship between state propaganda and violence; however, we do not find much evidence that these state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Josephine Lukito, Zhe Cui, An Hu, Taeyoung Lee, and João V. S. Ozawa (2022) open this thematic issue by exploring whether some states use and aggravate political polarization to their advantage. Using a combination of quantitative data from different sources, the authors study governments' responses to pro-democracy and proindependence protesters in young and non-democracies in East and Southeast Asia.…”
Section: Summaries Of Studies Included In This Thematic Issuementioning
confidence: 99%
“…Josephine Lukito, Zhe Cui, An Hu, Taeyoung Lee, and João V. S. Ozawa (2022) open this thematic issue by exploring whether some states use and aggravate political polarization to their advantage. Using a combination of quantitative data from different sources, the authors study governments' responses to pro-democracy and proindependence protesters in young and non-democracies in East and Southeast Asia.…”
Section: Summaries Of Studies Included In This Thematic Issuementioning
confidence: 99%
“…(Tran, 2023) revealed that the need for protection and validation of the actions of activists fighting for democracy can indirectly affect the ongoing participation of activists. (Lukito, Cui, Hu, Lee, & Ozawa, 2022) Shows that in dealing with protests through social media, the Tatmadaw carried out propaganda such as spreading false election claims and trapping the Tatmadaw with a bastion of democracy. Tatmadaw propaganda negatively framed the protesters as rioters, rebels, and even terrorists.…”
Section: Introductionmentioning
confidence: 99%